THE ROLE OF THE MEDICAL SOCIAL WORKER IN CONFRONTING RUMORS DIRECTED AGAINST VACCINES AGAINST THE EMERGING CORONA VIRUS (COVID 19). A DESCRIPTIVE STUDY APPLIED TO SOCIAL WORKERS IN HOSPITALS IN MAKKAH AL-MUKARRAMAH (CAHIERS MAGELLANES-NS, 2024)
This research explores the roles of medical social workers in addressing rumors directedagainst COVID-19 vaccines, focusing on a complete census of all female and malesocial workers (n=94) in Makkah hospitals. Employing the social survey method,data was collected from 90 individuals through a questionnaire. The studyreveals that the key responsibilities of medical social workers includeeducating individuals about the significance of COVID-19 vaccines anddispelling misconceptions surrounding them. Furthermore, the results highlightthe crucial skills employed by these professionals, emphasizing the formationof professional relationships and the provision of necessary awareness tocounteract rumors. The research underscores the importance of medical socialworkers conducting awareness campaigns to educate patients, their families, andthe local community about the dangers of rumors. Recommendations includemotivating individuals to receive vaccinations for the sake of community healthsecurity and enhancing the knowledge and skills of social workers in addressingvaccine-related misinformation. Additionally, emphasis is placed on leveragingmedia for disseminating information and educating citizens about the importanceof vaccination. This study contributes to the literature by shedding light onthe multifaceted role of medical social workers in the context of vaccinemisinformation during the COVID-19 pandemic.